RFA measurements of survival midpalatal orthodontic mini-implants in comparison to initial healing period - Manuel Nienkemper; Jan H. Willmann; Kathrin Becker; Dieter Drescher (SpringerOpen, 2020)
Abstract Background In dental implantology, the development of stability over time is a well-investigated topic. In case of orthodontic mini-implants, quantitative data for long-term stability is not available yet. This study aims to clinically investigate the long-term stability of mini-implants inserted in the midsagittal suture of the anterior palate. Moreover, the influence of the length of implants was elucidated. The stability of 2 × 9 and 2 × 11 mm mini-implants after orthodontic treatment (9 mm, 2.84 years ± 1.25 years; 11 mm, 3.17 years ± 0.96 years) was assessed by resonance frequency analysis (RFA). The obtained long-term pieces of data were compared with each other (9 mm vs 11 mm), as well as with the data from the matched early stability groups, to assess the initial and early secondary stability after the insertion from previous clinical trials. Results For both lengths, the long-term stability (2 × 9 mm, 25.12 ± 7.11, n = 21; 2 × 11 mm, 24.39 ± 5.82, n = 18) was significantly lower than primary stability (2 × 9 mm, 36.14 ± 6.08, n = 19; 2 × 11 mm, 33.35 ± 3.53, n = 20). The differences within the groups disappeared over the initial healing period: after 4 weeks for the 2 × 9 mm implants and after 2 weeks for the 2 × 11 mm implants. Also, the 2 × 9 mm and 2 × 11 mm implants showed comparable long-term stability values. Conclusion The stability of midpalatal mini-implants does not change in the long term after the initial healing period. Moreover, 2 × 9 mm mini-implants seem to be appropriate for orthodontic anchorage, as the stability of 2 × 11 mm implants is not higher. Therefore, owing to lower invasiveness, 2 × 9 mm implants should be preferred.